Intracranial Pressure Variability: A New Potential Metric of Cerebral Ischemia and Energy Metabolic Dysfunction in Aneurysmal Subarachnoid Hemorrhage?. Issue 2 (18th April 2023) - Svedung Wettervik, Teodor; Howells, Timothy; Hånell, Anders; Ronne-Engström, Elisabeth; Lewén, Anders; Enblad, Per
Abstract : Background: It was recently reported that lower intracranial pressure variability (ICPV) is associated with delayed ischemic neurological deficits and unfavorable outcomes in patients with aneurysmal subarachnoid hemorrhage (aSAH). In this study, we aimed to determine whether lower ICPV also correlated with worse cerebral energy metabolism after aSAH. Methods: A total of 75 aSAH patients treated in the neurointensive care unit at Uppsala University Hospital, Sweden between 2008 and 2018 and with both intracranial pressure and cerebral microdialysis (MD) monitoring during the first 10 days after ictus were included in this retrospective study. ICPV was calculated with a bandpass filter limited to intracranial pressure slow waves with a wavelength of 55 to 15 seconds. Cerebral energy metabolites were measured hourly with MD. The monitoring period was divided into 3 phases; early (days 1 to 3), early vasospasm (days 4 to 6.5), and late vasospasm (days 6.5 to 10). Results: Lower ICPV was associated with lower MD-glucose in the late vasospasm phase, lower MD-pyruvate in the early vasospasm phases, and higher MD-lactate-pyruvate ratio (LPR) in the early and late vasospasm phases. Lower ICPV was associated with poor cerebral substrate supply (LPR >25 and pyruvate <120 µM) rather than mitochondrial failure (LPR >25 and pyruvate >120 µM). There was no association between ICPV and delayed ischemic neurological deficit, but lower ICPV in both vasospasm phases correlated with unfavorable outcomes. Conclusion: Lower ICPV was associated with an increased risk for disturbed cerebral energy metabolism and worse clinical outcomes in aSAH patients, possibly explained by a vasospasm-related decrease in cerebral blood volume dynamics and cerebral ischemia.